1980
DOI: 10.1152/ajprenal.1980.238.3.f159
|View full text |Cite
|
Sign up to set email alerts
|

Renal handling of phenol red. IV. Tubular localization in rabbit and rat kidney in vivo

Abstract: In the rabbit kidney accumulation of phenol red in cortex tissue is directly related to phenol red excretion. In histological preparations of rabbit cortex the major part of phenol red is localized to the pars recta of proximal tubules at low plasma concentrations of dye. The extra uptake of dye by the pars recta is abolished by administration of a high dose of probenecid and also by high plasma dye concentrations, when dye secretion is low relative to tubular reabsorption. Tissue accumulation of phenol red in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

1982
1982
2004
2004

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
1
1
Order By: Relevance
“…The most notable observation in their study was that the uptake of L-proline by these vesicles, in contrast with the uptake of the amino acid by membrane vesicles isolated from adult rats, did not show an overshoot. The apparent discrepancy between our experimental results and those obtained by Goldmann et al (1979) on the mechanism of uptake of proline by luminal-membrane vesicles derived from newborn animals may be due to species difference, since it has been reported that the tubular localization of Phenol Red in rat and rabbit kidney is basically different (Sheikh & M0ller, 1980). However, it seems reasonable to avoid further speculation on this before a more detailed study on the renal uptake of proline in newborn animals is provided.…”
Section: Resultscontrasting
confidence: 99%
“…The most notable observation in their study was that the uptake of L-proline by these vesicles, in contrast with the uptake of the amino acid by membrane vesicles isolated from adult rats, did not show an overshoot. The apparent discrepancy between our experimental results and those obtained by Goldmann et al (1979) on the mechanism of uptake of proline by luminal-membrane vesicles derived from newborn animals may be due to species difference, since it has been reported that the tubular localization of Phenol Red in rat and rabbit kidney is basically different (Sheikh & M0ller, 1980). However, it seems reasonable to avoid further speculation on this before a more detailed study on the renal uptake of proline in newborn animals is provided.…”
Section: Resultscontrasting
confidence: 99%
“…Nonetheless, phenol red clearance remained in use for many years as a test of renal function (19,20). High fractional clearance of protein-bound solutes like phenol red is achieved by active solute transport into the tubular lumen (21). Free solute levels in the renal interstitium are pumped down low enough so that a large portion of bound solute dissociates from plasma proteins during the few seconds that blood transits the kidney.…”
Section: Discussionmentioning
confidence: 99%